2020
DOI: 10.1139/cjm-2019-0531
|View full text |Cite
|
Sign up to set email alerts
|

The yeast, the antifungal, and the wardrobe: a journey into antifungal resistance mechanisms ofCandida tropicalis

Abstract: Candida tropicalis is a prominent non-Candida albicans Candida species involved in cases of candidemia, mainly causing infections in patients in intensive care units and (or) those presenting neutropenia. In recent years, several studies have reported an increase in the recovery rates of azole-resistant C. tropicalis isolates. Understanding C. tropicalis resistance is of great importance, since resistant strains are implicated in persistent or recurrent and breakthrough infections. In this review, we address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 112 publications
0
13
0
4
Order By: Relevance
“…Based on clinical practice guidelines [ 4 , 6 ] and our in vitro AFST data, echinocandins should be considered as the first choice for initial treatment of most episodes of candidemia and invasive candidiasis, except for central nervous system, eye, and urinary tract infections due to Candida . In addition, we observed an obvious cross resistance of C. tropicalis to fluconazole and voriconazole that may be related to different azole target Erg11p modifications or increased efflux pump activity [ 22 ]. On a larger scale, further study of the molecular mechanism of antifungal resistance, continuous antifungal resistance surveillance, development of non-cultured rapid diagnostic methods, and antifungal stewardship will be necessary to improve antifungal drug-resistant predicaments [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on clinical practice guidelines [ 4 , 6 ] and our in vitro AFST data, echinocandins should be considered as the first choice for initial treatment of most episodes of candidemia and invasive candidiasis, except for central nervous system, eye, and urinary tract infections due to Candida . In addition, we observed an obvious cross resistance of C. tropicalis to fluconazole and voriconazole that may be related to different azole target Erg11p modifications or increased efflux pump activity [ 22 ]. On a larger scale, further study of the molecular mechanism of antifungal resistance, continuous antifungal resistance surveillance, development of non-cultured rapid diagnostic methods, and antifungal stewardship will be necessary to improve antifungal drug-resistant predicaments [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like C. albicans, C. tropicalis causes superficial mucosal infections, as well as disseminated and deep-seated infections; the rising incidence of azole-resistant C. tropicalis is causing clinical concern (reviewed in de Oliveira et al, 2020). Previous reports about C. tropicalis ALS genes suggested that the family is larger in this species than in other common fungal pathogens (Butler et al, 2009;Jackson et al, 2009), representing perhaps the most challenging ALS family puzzle to solve.…”
Section: Introductionmentioning
confidence: 99%
“…[1] , 至今为止,除南极洲以外,该酵母菌已经在其它六大洲的 40 多个国家被报道 [2] 。耳念珠菌感 染可以发生在各个年龄段的人群,其中在老年人中最为常见, 新生儿和儿童也偶有感染 [3,4,5] 。 耳念珠菌常见的宿主可以分为三类: 一是患有严重免疫缺陷疾病或自身免疫能力较弱的人群, 二是开放性手术患者或侵入性导管使用患者,三是使用广谱抗菌药物治疗的人群 [6] 。研究表 明,耳念珠菌可以引起多种侵袭性感染,包括血液感染、尿路感染、皮肤感染和下呼吸道感 染,尤其容易感染患有严重高血压、肾脏病等疾病的患者 [6] 。尽管耳念珠菌首先在外耳道内 发现,但是它可以在患者的皮肤表面长期定殖,通常定殖在腋窝、腹股沟和鼻孔处 [7] ;其在 医疗保健环境中也可以长时间存活,如在医疗设备、病床、地板等处都可以持久生存,对常 见的医疗消毒剂具有很高的耐受力,所以容易造成传播,常常导致耳念珠菌在医院内爆发感 染 [6] 。耳念珠菌具有耐热性,其最适生长温度为 37℃,在 40℃和 42℃下仍然可以生长 [8] ;此 外,对高盐浓度的耐受性也是耳念珠菌的一个重要特征 [6] 。在临床治疗方面,大多数耳念珠 菌具有多重耐药性,其中包括三大类主要的抗真菌药物--唑类药物、多烯类药物和棘白菌素 类药物。因此,耳念珠菌感染的治愈难度高,给临床治疗带来了严峻挑战。追溯耳念珠菌的 鉴定历史发现,2009 年以前几乎未见报道,迄今为止发现最早的耳念珠菌分离物是在 1996 年 [9] ,尽管当时研究显示该菌可能是一种新出现的致病性真菌,但是关于其能够在短期内迅 速广泛感染人类的原因尚不清楚。基因组分析显示,在过去的 400 年里,除了南极洲以外的 六大洲不同的地理位置几乎同时出现了耳念珠菌不同的谱系 [10] ,主要分为四个分支:南亚分 支(I),东亚分支(II),非洲分支(III)和南美分支(IV) [11,12] 。全基因组分析表明,不同的分支 之间基因组多样性差别很大,差异多达数十万个碱基对,但每个分支内的基因组序列差别较 小,多为近亲克隆菌株。近来,Chow 等报道了第五个分支--伊朗分支(Ⅴ) [13] [35,36,37] ,是由糖蛋白、碳水化合物、多糖等组成的胞外结构 [38] 。生物膜在感染宿主的过程中至 关重要,位于生物膜中的细胞能更好地抵抗药物或外界影响,逃避宿主免疫系统的攻击 [79] 。麦角甾醇功能的紊乱被认为是多烯类药物抑制真菌的重要机制 [80] 。…”
Section: 耳念珠菌(C Auris)是在 2009 年从一位日本女性患者的外耳道中被发现的病原真菌unclassified